Superconductor Microwave Kinetic Inductance Detectors: System Model of the Readout Electronics - F. Alimenti; M. Ercoli; V. Palazzari; L. Roselli (Radioengineering, 2009)
This paper deals with the readout electronics needed by superconductor Microwave Kinetic Inductance Detectors (MKIDs). MKIDs are typically implemented in the form of cryogenic-cooled high quality factor microwave resonator. The natural frequency of these resonators changes as a millimeter or sub-millimeter wave radiation impinges on the resonator itself. A quantitative system model of the readout electronics (very similar to that of a vector network analyzer) has been implemented under ADS environment and tested by several simulation experiments. The developed model is a tool to further optimize the readout electronic and to design the frequency allocation of parallel-connected MKIDs resonators. The applications of MKIDs will be in microwave and millimeter-wave radiometric imaging as well as in radio-astronomy focal plane arrays.